Uses and Effects of Religious Programs among Yemeni Audiences - Al-Shami, Abdurahman M (Jurnal Komunikasi Islam, 2013)
Abstract: The study aims to contribute to the current under–standing of how audiences make use of religious programs broadcasted in both religious satellite channels (RSCs) and Arabic satellite channels. 210 respondents were surveyed to address the nature of exposure to RSCs and religious pro–grams, motives, and attitudes toward them. Utilizing uses and effect approach and Hall’s encoding and decoding model of media discourses, this study confirms a high expo–sure to RSCs among adult television viewers in Yemen. Of religious contents, Islamic lectures particularly represent the most watched program by respondents. It also states that emotional effects represent the prominent effects of religious programs uses followed by normative, and limited beha–vioral effects.Keywords: religious programs, uses and effects approach, Hall's encoding/decoding model, Yemeni audience.